2012
DOI: 10.1186/1743-422x-9-104
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous virulence of pandemic 2009 influenza H1N1 virus in mice

Abstract: BackgroundUnderstanding the pathogenesis of influenza infection is a key factor leading to the prevention and control of future outbreaks. Pandemic 2009 Influenza H1N1 infection, although frequently mild, led to a severe and fatal form of disease in certain cases that make its virulence nature debatable. Much effort has been made toward explaining the determinants of disease severity; however, no absolute reason has been established.ResultsThis study presents the heterogeneous virulence of clinically similar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Although the difference of amino acids did not match the known functional sites associated with pathogenicity in mice, these novel viruses possessed six common amino acid changes in HA, PA, PB2 and NS1 proteins compared with human 2009/H1N1 strains. Some of the above mutations were similar to the molecular changes of 2009/H1N1 virus reported by other researchers [23,35]. It is reported that the HA, PB2, PA and NS genes of 2009/H1N1 are in the classical swine lineage derived from the 1918 Spanish pandemic virus, and many viral mutations associated with the pathogenicity and cross-species transmission of 2009/H1N1 are present in these viral proteins, e.g., D222G in HA [36], T271A in PB2 [37], T552S in PA [38] and E125D in NS1 [39].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although the difference of amino acids did not match the known functional sites associated with pathogenicity in mice, these novel viruses possessed six common amino acid changes in HA, PA, PB2 and NS1 proteins compared with human 2009/H1N1 strains. Some of the above mutations were similar to the molecular changes of 2009/H1N1 virus reported by other researchers [23,35]. It is reported that the HA, PB2, PA and NS genes of 2009/H1N1 are in the classical swine lineage derived from the 1918 Spanish pandemic virus, and many viral mutations associated with the pathogenicity and cross-species transmission of 2009/H1N1 are present in these viral proteins, e.g., D222G in HA [36], T271A in PB2 [37], T552S in PA [38] and E125D in NS1 [39].…”
Section: Discussionsupporting
confidence: 86%
“…Many investigators have concentrated on the pathogenicity of 2009/H1N1 isolates in a mice model, and found that most of the tested 2009/H1N1 viruses show low lethality in mice, only at the highest dose of 10 6.5 EID 50 or PFU, though they could cause more severe pathological lesions in lungs than currently seasonal A(H1N1) viruses [14,15,21,22]. Most strikingly, researchers recently isolated some 2009/H1N1 variants with certain amino acid mutations, and infection experiments showed that these variants could induce approximately 40%-100% lethal response in mice even at the lower doses [10,23,24], which indicates that 2009/H1N1 viruses possess a potential phenotypic variability in the evolutionary process.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of CXCL14 does not affect the severity of the infection with either influenza virus or E. coli. CXCL14-deficient and wild type control mice were intranasally infected with A) 10 3 EID 50 of influenza PR8 (n=12 per group), and B) 10 4 EID 50 of influenza A/Mexico/4108/09 (n=12 per group); the weight loss and the survival rate were monitored over the first 14 days post infection. C) Histopathological evaluation of the lung tissue from mice infected with PR8, 6 days post-infection.…”
Section: Cxcl14 Deficiency Does Not Impact the Outcome Of Influenza Imentioning
confidence: 99%
“…-/-and wildtype C57B6/129 mice (WT) were infected with 10 4 EID 50 of A/Mexico/4108/2009 and 10 3 EID 50 of A/Puerto Rico/8/1934 (ATCC #VR-95) (PR8), as previously described [10].…”
Section: Influenza Infectionmentioning
confidence: 99%
“…. A human lung epithelial cell line known as A549 (one of the permissive cell lines to influenza virus infection) has been widely used to study the viral replication kinetics and host response to virus infection (Farooqui et al, 2012;.…”
Section: A549 and Cef)mentioning
confidence: 99%